Conventional brain magnetic resonance imaging in the longitudinal evaluation of newly diagnosed systemic lupus erythematosus patients: a retrospective analysis from a single-centre cohort. (April 2020) - Silvagni, E; Bortoluzzi, A; Borrelli, M; Padovan, M; Furini, F; Govoni, M
Introduction: Neuropsychiatric (NP) manifestations occur mostly in the early phases of the systemic lupus erythematosus (SLE) course. Nonspecific alterations are evident in conventional brain magnetic resonance imaging (MRI), regardless of clinically overt NP symptoms. The main aims of this study were to assess the prevalence of MRI abnormalities in newly diagnosed SLE, and to evaluate the impact of MRI changes during follow-up (FU) and the clinical course of NP symptoms. Materials and methods: Newly diagnosed SLE patients with a baseline brain MRI and with available repeated MRI during FU were retrospectively evaluated. White-matter lesions and atrophy were recorded, comparing NPSLE and non-NPSLE patients. Cox proportional hazard models were used to compare NP events during FU with MRI data. Results: Forty-four patients were included, 22 with NP events attributed to SLE. The baseline MRI scan was abnormal in 21 patients (47.73%). New NP events occurred in 17 patients, and worsening was found in repeated MRIs in 12 (27.27%). A worsening of MRI was associated with higher occurrence of new NP events during FU (adjusted hazard ratio 3.946 (1.175–13.253)). Conclusion: Baseline MRI is useful in patients with an early diagnosis of SLE, allowing comparison with subsequent scans. In our study, radiological worsening of repeated brain MRI was associated with new NP events.